Perlindungan Hukum Bagi Nasabah dan Bank Terhadap Tindak Kejahatan Berbasis Teknologi Informasi (Cyber Crime) - See, Benedictus Renny (Jurnal Hukum Caraka Justitia, 2022)
Banks as intermediary institutions and trust institutions as the driving force of a country's economy, in their activities, cannot be separated from the use of information technology to support their operations. The use of information technology by banks in addition to having a positive impact also has a negative impact that will threaten and harm the bank and its customers, if not managed properly. Banking crimes that use information technology, especially against bank products and services that use computers and internet networks (Cybercrime) will cause losses to customers and the bank itself.This research is normative juridical research that is descriptive-analytical with a case approach to identify and analyze forms of crime in the banking world and the efforts made by the government CQ. financial authorities in providing legal protection for customers and banks from criminals who use information technology.The results of this study indicate that cybercrime is a crime using information technology that can be carried out without recognizing territorial boundaries and no direct interaction between perpetrators and victims of crime is required; so that the government, as well as the monetary authority (BI) and the Financial Services Authority (OJK) as supervisors in the financial and banking sectors, need to protect the public (customers) and banking institutions, namely by taking preventive and repressive actions by implementing existing laws and regulations and coordinating with law enforcement officers in preventing the occurrence of Cybercrime and providing severe penalties for the perpetrators of these crimes.